2006
DOI: 10.1207/s15473341lld0203_1
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Old Puzzles From Infants' Categorical Discrimination of Soundless Phonetic Units

Abstract: For 4 decades, serious scientific debate has persisted as to whether infants' remarkable capacity to detect and categorize phonetic units is derived from language-specific mechanisms or whether this capacity develops out of general perceptual mechanisms. The heart of this controversy has revolved around whether the young human brain is specialized to detect the underlying contrasting patterns in language or whether it simply processes general auditory perceptual features of sound that, over time, become utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 54 publications
(54 reference statements)
6
68
1
Order By: Relevance
“…This brings us to the issue of developmental accounts of perceptual learning (Werker, 1994). If categorical perception of handshape contrasts is present from birth, as Baker et al (2006) have argued, and is subsequently lost by 14 months of age in individuals without exposure to sign, then we should find low levels of discrimination performance on both within- and between-category contrasts for deaf non-native and hearing L2 signers. By this account, the native signers should distinguish themselves as the only group with unusually good discrimination at identification boundaries.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This brings us to the issue of developmental accounts of perceptual learning (Werker, 1994). If categorical perception of handshape contrasts is present from birth, as Baker et al (2006) have argued, and is subsequently lost by 14 months of age in individuals without exposure to sign, then we should find low levels of discrimination performance on both within- and between-category contrasts for deaf non-native and hearing L2 signers. By this account, the native signers should distinguish themselves as the only group with unusually good discrimination at identification boundaries.…”
Section: Discussionmentioning
confidence: 83%
“…These studies contradict the first investigation of categorical perception in ASL, in which Supalla & Newport (1975, as reported in Newport, 1982) found no evidence of categorical perception of either handshape or POA by native signers. Subsequently, Baker, Golinkof & Petitto (2006) tested discrimination of one handshape contrast by 4-month-old and 14-month old hearing infants with no prior sign exposure, and found that only the younger of these two groups discriminated the handshape contrast. These authors draw a parallel between studies showing sensitivity to spoken language contrasts in infancy that are subsequently lost in speakers without exposure to those contrasts, such as loss of sensitivity to the retroflex /T/-/t/ distinction by English speakers (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is behavioral evidence from Baker, Golinkoff, and Petitto (2005) that 4-monthold hearing (speech-exposed) infants, who have no exposure to a signed language, can categorically discriminate phonetic handshape units in ASL. The infants also have no relevant experience with the handshape contrasts, which were a subset of the stimuli used in the present study, and thus cannot be using category labels for discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…As in spoken phonology, signed phonological systems encode the hierarchical organization of discrete distinctive features (Brentari, 1998; Sandler and Lillo-Martin, 2006), they represent the syllable—a prosodic unit that is demonstrably distinct from a morpheme (Brentari, 1998; Sandler and Lillo-Martin, 2006), and constrain their sonority profile (Stokoe, 1960; Klima and Bellugi, 1979; Corina, 1990; Perlmutter, 1992; Brentari, 1993, 1994, 1998; Corina and Sandler, 1993; Brentari, 2006; Sandler and Lillo-Martin, 2006; Sandler, 2008; Jantunen and Takkinen, 2010; Wilbur, 2012). Experimental research on sign languages has further shown that signers—both adults (Lane et al, 1976; Newport, 1982; Hildebrandt and Corina, 2002; Emmorey et al, 2003; Baker et al, 2005; Best et al, 2010) and infants (Baker et al, 2006; Palmer et al, 2012)—encode phonological features as phonetic categories, subject to perceptual narrowing in the first year of life (Baker et al, 2006; Palmer et al, 2012). Moreover, distinct feature classes differ in their contribution to language processing.…”
Section: Introductionmentioning
confidence: 99%